Drivers of professional fulfillment and burnout among emergency medicine faculty: A national wellness survey by the Society for Academic Emergency Medicine. (22nd April 2022) - Lu, Dave W.; Lee, Justin; Alvarez, Alai; Sakamoto, Jeffrey T.; Bird, Steven B.; Sundaram, Vandana; Lall, Michelle D.; Nordenholz, Kristen E.; Manfredi, Rita A.; Blomkalns, Andra L.
Abstract: Background: Professional fulfillment and the mitigation of burnout can enhance clinician well‐being and the resiliency of the health care organization. This study examined the extent to which specific individual and workplace factors are associated with professional fulfillment and burnout among a national sample of academic emergency physicians. Methods: This was a cross‐sectional survey of faculty members of the Society for Academic Emergency Medicine. Primary outcomes were professional fulfillment and burnout. The survey also examined individual and workplace factors as well as faculty's thoughts of attrition from academic and clinical medicine. Logistic regression was performed to determine the relationships between each outcome and each factor, respectively. Results: A total of 771 of 3130 faculty completed the survey (response rate 24.6%). A total of 38.7% reported professional fulfillment and 39.1% reported burnout. Meaningfulness of work (odds ratio [OR] 2.2, 95% confidence interval [CI] 1.9–2.5), perceived appreciation (OR 1.9, 95% CI 1.7–2.1), and the academic work environment (OR 1.7, 95% CI 1.5–1.9) had the highest odds of being associated with professional fulfillment. In contrast, low score responses for meaningfulness of work (OR 0.6, 95% CI 0.5–0.6), self‐compassion (0.6, 95% CI 0.5–0.6), and control over schedule (OR 0.6, 95% CI 0.6–0.7) were most associated with burnout. Faculty with professional fulfillment were less likely to report plans for attrition from academics (OR 0.1, 95% CI 0.1–0.2) and from clinical medicine (OR 0.2, 95% CI 0.1–0.4). Faculty with burnout were more likely to report plans for attrition from academics (OR 7, 95% CI 4.8–10.4) and clinical medicine (OR 5.7, 95% CI 3.9–8.6). Conclusions: Individual and workplace factors that contributed to professional fulfillment and burnout were identified, with meaningfulness of clinical work demonstrating the strongest association with both occupational phenomena. Knowledge of which factors are most impactful in promoting professional fulfillment and mitigating burnout may be useful in guiding efforts to enhance clinician well‐being.